(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores strategies for enhancing the efficiency of investment activities in agricultural enterprises. It investigates the factors influencing investment success and presents practical methods for optimizing investment returns, ensuring sustainable development, and supporting economic stability in the agricultural sector.